Small-molecule inhibition of STOML3 oligomerization reverses pathological mechanical hypersensitivity - Wetzel, Christiane; Bali, Kiran Kumar; Kuner, Rohini (Nature neuroscience, 2017)
The skin is equipped with specialized mechanoreceptors that allow the perception of the slightest brush. Indeed, some mechanoreceptors can detect even nanometer-scale movements. Movement is transformed into electrical signals via the gating of mechanically activated ion channels at sensory endings in the skin. The sensitivity of Piezo mechanically gated ion channels is controlled by stomatin-like protein-3 (STOML3), which is required for normal mechanoreceptor function. Here we identify small-molecule inhibitors of STOML3 oligomerization that reversibly reduce the sensitivity of mechanically gated currents in sensory neurons and silence mechanoreceptors in vivo. STOML3 inhibitors in the skin also reversibly attenuate fine touch perception in normal mice. Under pathophysiological conditions following nerve injury or diabetic neuropathy, the slightest touch can produce pain, and here STOML3 inhibitors can reverse mechanical hypersensitivity. Thus, small molecules applied locally to the skin can be used to modulate touch and may represent peripherally available drugs to treat tactile-driven pain following neuropathy.